Long-Term Nitrogen and Phosphorus Fertilization of Irrigated Corn - A. Schlegel; H. D. Bond (Kansas Agricultural Experiment Station Research Reports, 2018)
This study was initiated in 1961 to determine responses of continuous corn and grain sorghum grown under flood irrigation to N, P, and potassium (K) fertilization. The study is conducted on a Ulysses silt loam soil with an inherently high K content. No yield benefit to corn from K fertilization was observed in 30 years, and soil K levels remained high, so the K treatment was discontinued in 1992 and replaced with a higher P rate.
Keywords: Nitrogen fertilization; phosphorus fertilization; irrigated corn; long-term fertility; nutrient removal